Miniinvasive Approach in the Complex Treatment of Tumor and Stone Etiology of Mechanical Jaundice - Nurboboyev Adkhambek Uygunovich; Makhmudova Guljamol Fazliddinonvna (Research Parks Publishing LLC, 2021)
the use of miniinvasive technologies and step-by-step methods of surgical treatment in patients with mechanical jaundice with gall stone disease can reduce mortality and the number of complications after surgery to 3.4% and 14.1%, respectively, in biliopan creatoduodenal zone tumors to 2.9% and 19.6%.